Concept art design for the Mayapada culinary digital game Nusa dan Tara in pixel art style: Perancangan concept art gim digital kuliner Mayapada Nusa dan Tara dengan gaya pixel art - Widadijo, Wahyu Tri; Tanudjaja, Aphrodite (Universitas Negeri Yogyakarta, 2025)
This study designs concept art for a digital game introducing traditional Indonesian cuisine to urban teenagers, whose interest has declined due to globalisation and fast food culture. The game features 2D pixel art and gamification to create an engaging learning experience. A design-based methodology was used, covering orientation, analysis, concept, design, and implementation. Data were collected through observation and literature on Nusantara cuisine, folklore, and traditional houses. The 5W+1H method guided the analysis of issues and audience needs. The result is a set of visual assets, including character designs (main character, story NPCs, supporting NPCs), environments (modern restaurants and the parallel world of Mayapada Nusantara), and props (dishes and ingredients). Character designs adopt fairy tale subversion, and environmental design applies top-down and visual dissonance techniques. The study contributes to educational game development and promotes a culturally rich pixel art visual style. _______________________________________________________________________________ Penelitian ini merancang concept art gim digital bertema kuliner tradisional Nusantara untuk remaja kota besar yang kurang tertarik pada kuliner lokal akibat globalisasi. Gim dirancang dengan gaya pixel art 2D dan pendekatan gamifikasi untuk menciptakan pengalaman belajar yang menyenangkan. Metode perancangan desain digunakan melalui tahap orientasi, analisis, konsep, desain, dan implementasi. Data diperoleh dari observasi dan studi literatur tentang kuliner, cerita rakyat, dan rumah adat. Analisis dilakukan dengan metode 5W+1H. Hasilnya berupa aset visual meliputi desain karakter (tokoh utama, NPC cerita, NPC pendukung), lingkungan (restoran modern dan dunia paralel Mayapada Nusantara), serta properti (makanan dan bahan masakan). Konsep karakter didasarkan pada teori subversi dongeng, sementara lingkungan memakai pendekatan top-down dan disonansi visual. Penelitian ini memberi kontribusi pada pengembangan gim edukatif dan gaya pixel art lokal.